Implementasi Undang-Undang tentang Pertambangan Mineral dan Batu Bara terhadap Tindak Pidana Perbuatan Curang (Bedrog) pada Pertambangan Batu Bara - Vika Nur Senda (Savana, 2025)
Implementation of Law Number 3 of 2020 on Mineral and Coal Mining in the Context of Frauduelent Acts (Bedrog) in the Coal Mining Sector. This law aims to strengthen the regulation and enforcement of laws against illegal mining activities, which are rampant in Indonesia and often harm the state and the environment. This study uses a normative juridical method with an analysis of the applicable legal provisions, including regulations on sanctions for those who conduct mining without permits. The results of the study show that there are several forms of criminal acts regulated by the law, such as unlicensed mining, submission of false data, and failure to conduct reclamation. Law enforcement against these violations still faces challenges, especially in terms of effective supervision and enforcement. Although there are clear criminal sanctions, illegal mining practices continue, highlighting the need to improve the capacity of law enforcement officers and foster collaboration among related institutions. The conclusion of this study emphasizes the importance of applying the principles of transparency and accountability in natural resource management, as well as the need for reforms in the licensing system to prevent criminal acts in the mining sector. Therefore, the implementation of Law Number 3 of 2020 is expected to have a positive impact on reducing illegal mining practices and protecting the environment.